On the Hidden Costs of Incentive Schemes - Dirk Sliwka (Institute for the Study of Labor (IZA), 2003)
By enriching a principal-agent model it is shown that the introduction of monetary incentives may reduce an agent?s motivation. In a first step, we allow for the possibility that some agents stick to unverifiable agreements. The larger the fraction of reliable agents, the lower powered will then be the optimal incentive scheme and fixed wages become optimal when performance measurement is costly. If social norms matter such that some agents? reliability is influenced by their beliefs on the convictions of others, high powered incentives signal that not sticking to agreements is a widespread behavior and may lead to lower effort levels.
Keywords: J33; M52; D23; 330; incentives; intrinsic motivation; motivation crowding-out; honesty; Leistungsanreiz; Anreizvertrag; Theorie